Analisis Spasial Temporal dan Trend Perubahan Land Surface Temperature Menggunakan Google Earth Engine - Tripaldi, Agus; Maru, Rosmini; Sideng, Uca; Hasriyanti, Hasriyanti; Malik, Abdul; Djirong, Agussalim (Jurnal Penelitian Pendidikan Geografi, 2026)
Gorontalo City has recently experienced weather anomalies, with air temperatures reaching 35.2°C, the highest recorded in the last three decades. This study aims to describe the trend and spatial distribution of land surface temperature (LST) in Gorontalo City. Data were analyzed using Google Earth Engine through a spatial–temporal descriptive approach. The results show that the city’s LST has increased, indicated by the expansion of the very high temperature category from 5% in 2014, to 40% in 2019, and 47% of the total area in 2024. This increase is more pronounced in the northern part of the city, particularly in Kota Utara and Kota Barat Districts, which exhibit the highest temperatures. The trend analysis further reveals that the very high LST class experienced the most significant rise over the 2014–2024 period (slope +1.581; R² = 0.87), while the high LST class declined due to class shifting toward very high. These findings may serve as a reference for strengthening urban green space planning and management in Gorontalo City to mitigate temperature escalation resulting from rapid land conversion and urban development.